POHON URBAN BLORA: RUANG REHAT UNTUK KOMUTER DI JALAN BLORA - Juan Valentino Lumanauw; Agustinus Sutanto (Jurusan Arsitektur dan Perencanaan, 2023)
Blora Street is a road in the Menteng area, Central Jakarta. This street is famous for its shops which are lined up along Jalan Sudirman. However, due to a change in the configuration of the Jalan Blora area, the movements that occur are also changing, and this causes the area to no longer be as busy as it used to be. For this reason, an architectural approach by means of urban acupuncture is used to try to revive an area that is increasingly losing its hustle and bustle. This project is located on one of the vacant lands in the Blora street shopping strip. This project proposes the construction of a break room to meet the community's need for open space as well as a transit space for the community to take a short break from work and the commuting lifestyle they always do. This project aims to provide a space for people to